Characterization of Lateritic Banka Gravelous (West Cameroon) for Their Use in Road Geotechnical - Jules Hermann, Keyangue Tchouata; Casimir, Gouafo; Valentine Yato, Katte; François, Ngapgue; Cédric, Djambou-Tchiadjeu; Grégoire, Kamdjo; Gouafo Mathurin, Zoyem (American Scientific Research Journal for Engineering, Technology, and Sciences, 2019)
In Cameroon, as in most tropical countries, the use of lateritic gravel in road construction is of great interest because of its abundance. The locality of Banka located in the department of Haut-Nkam (West-Cameroon) abounds several lateritic zones with little known characteristics. These lateritic materials are however very popular in the locality for their main use in the periodic maintenance of unpaved roads. The geotechnical identification tests carried out on 18 samples taken from the Banfeko, Bakoye and Ketcho sites have shown that the density values of the solid grains are greater than 2.57 g / cm3. The values of the plasticity indices are between 17.89 and 25.38 and those of consistency between 1,56 and 2.12 for these gravelly lateritic plastic consistency to firm. Granulometric analysis shows that the fines are less than 35%. The optimum water content values for compaction with modified Proctor energy are between 11% and 14% and those for dry optimum densities around 2.1. The values of the CBR lift index are between 31 and 51.92. These soils are subclass B6 according to the GTR and subclasses A-2-7 (1) and A-2-7 (2) according to the HRB. The particle size curves of the various samples analyzed are relatively well inscribed in the reference spindles of the materials recommended by the CEBTP for the road construction as a base course and as a base layer for these soils of the S5 lift class. But their use as a base layer requires an improvement of the bearing capacity, because the value of the CBR remains less than 80 to 95% of the modified Proctor optimum.